Analisis Penerapan Pasal 362 JO Pasal 64 Ayat (1) KUHP dalam Tindak Pidana Pencurian Emas: Studi terhadap Putusan Pengadilan Negeri Nomor 170/Pid.B/2023/PN Kpg - Amanda Lastiningsi Pura Ndima; Deddy R. CH. Manafe; Adrianus Djara Dima (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study examines the application of Article 362 jo Article 64 paragraph (1) of the Criminal Code (KUHP) in the Kupang District Court Decision Number 170/Pid.B/2023 against the defendant Sherly Oktaviana Nggeon, who was proven to have committed the crime of repeatedly stealing gold at her workplace, Toko Mas Sahabat. This study aims to assess the accuracy of the application of criminal law norms to concrete facts revealed at the trial and analyze the judge's considerations both from juridical and non-juridical aspects in imposing a verdict. The method used is a normative juridical approach with secondary data sources obtained through literature studies of laws and regulations, doctrines, and court decisions. The results of the study show that although the panel of judges has formally applied Article 362 jo Article 64 paragraph (1) of the Criminal Code by qualifying the defendant's actions as a continuing act (voortgezette handeling), this approach is not entirely appropriate substantively. The act of theft was carried out in different periods, against different objects, and accompanied by the forgery of a memorandum of sale of elements that can legally be qualified as a separate criminal offense based on Article 263 of the Criminal Code. However, in the judge's decision, this act of forgery was not explicitly considered either as an additional charge or as a burden of punishment. This raises the issue of justice, considering that the merging of all acts into one criminal act reduces the weight of criminal responsibility that the defendant should receive, and does not fully reflect the overall dimension of the crime committed. From a non-juridical aspect, the judge considered the defendant's background, good faith to return the damages, and the social and economic conditions of the defendant in imposing a two-year prison sentence. However, this consideration is considered disproportionate when compared to the amount of loss, the consistency of the evil act, and the existence of counterfeiting which contributes to aggravating the character of the crime. This study emphasizes the importance of a more comprehensive legal approach in qualifying compound crimes (concursus realis), as well as the need for judges to